(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
R. K. Narayan was one of the most important writers of Indian literature in English. In his writing, we saw a range of Indian socioeconomic issues. He has written on a variety of sensitive topics, such as poverty, illiteracy, and the caste system. The Guide, R.K. Narayan’s best-known book, examines the goals of Indian youth and society. The novel Guide, which is adapted into the film, depicts the aspirations of Indian society and young people. Movies are always drawn to literature, and many films are based on these works. Filmmakers were drawn to R. K. Narayan’s novel because it attempted to depict the ambitions of Indian youth. The goals and convictions of Raju, the primary character, are presented in this paper. Raju’s journey from a criminal to a sadhu is the central premise of both the book and the film. A comparative analysis of The Guide and its film version rounds off the paper.